Household membership decisions of adult children - Maria Concetta Chiuri; Daniela Del Boca (Institute for the Study of Labor (IZA), 2008)
While several social, economic and financial indicators point to a growing convergence among European countries, striking differences still emerge in the timing of leaving home for adult children. In Southern countries (as Spain, Italy or Portugal) in 2001 more than 70 percent of young adults between 18 and 34 years of age live with their parents, whereas the corresponding number for Northern countries (like Denmark or the UK) is well below 40 percent. Existing literature highlights several factors explaining the different patterns in Europe: preferences and culture, labor market conditions, housing market as well as differences across the welfare states. In our work, we consider living arrangements of people 18-34 years old from 14 European countries (ECHP). We augment the informational content with indicators of labor, housing and marriage markets characteristics as well as proxy for the welfare states and culture. We investigate how they are intertwined with gender differences.
urn:nbn:de:101:1-20080619226
Keywords: J13; 300; Living arrangements; duration analysis; government expenditures; Familie; Erwachsene; Familiensoziologie; Sozialstaat; Kulturpsychologie; Statistische Bestandsanalyse; EU-Staaten